Indentation response of a NiTi shape memory alloy: modeling and experiments - C. Maletta; F. Furgiuele; E. Sgambitterra; M. Callisti; B. G. Mellor; R. J. K. Wood (Fracture and Structural Integrity)
The indentation response of a pseudoelastic nickel-titanium based shape memory alloy (SMA) has been analyzed. Indentation tests have been carried out at room temperature using a spherical diamond tip and indentation loads in the range 50-500 mN in order to promote a large stress-induced transformation zone in the indentation region and, consequently, to avoid local effects due to microstructural variations. The measured load-displacement data have been analyzed to obtain information on the pseudoelastic response of the alloy. To aid this analysis numerical simulations were performed, by using a commercial finite element (FE) softwarecode and a special constitutive model for SMAs, so as to understand better the microstructural evolution occurring during the indentation process. Finally, the FE model has been used to analyze the effects of temperature on the indentation response of the alloy. This analysis revealed a marked variation of both the maximum and residual penetration depths with increasing test temperature.